ENSEMBLE APPROACH IN DESIGN SOLUTIONS FOR FURNISHING REHABILITATION FACILITIES - Novik, Hanna; Gnatiuk, Liliia; Pylypenko, Nataliia (Theory and practice of design, 2025)
Purpose. The purpose of this article is to substantiate the concept of ensemble design in furniture for rehabilitation facilities, emphasizing the importance of a holistic approach to spatial environment development in order to enhance functionality, psychological comfort, and aesthetic integrity in spaces tailored to the needs of users with special requirements. Methodology. The study is based on a comprehensive approach that includes the analysis of contemporary design practices, principles of ergonomics, inclusive design, and observational methods. Elements of visual analysis of furniture ensembles and typological modeling are applied. Results. The article identifies key approaches to ensemble design that are appropriate for rehabilitation spaces. A typical classification of furniture elements is proposed, and the need for a harmonious combination of aesthetics and ergonomics is substantiated. The role of holistic design in ensuring patients’ emotional well-being and the efficient work of personnel is defined. Scientific novelty. For the first time, the concept of ensemble design is systematized in the context of furniture design for rehabilitation institutions. The author proposes a model of interconnection between elements of a furniture ensemble and the functional-psychological structure of space. Practical relevance. The results of the study can be applied in the professional activities of interior designers and architects, as well as in the development of educational programs in the «Design» field, particularly in the «Environmental Design» and «Industrial Design» specializations.